(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The Protection of Women from Sexual Harassment (POSH) Act, 2013 mandates that everycompany develop anti-sexual harassment policy for its staff. Despite this many workforces are abstainedfrom its rights under the POSH Act, due to poor enforceability. This legitimately contributes to the rise inoccurrences of sexual harassment cases despite a dedicated legislation which ought to have beenpreventing sexual harassment.